Determination Of Subsurface Aquifers and Distribution of Groundwater Table Depth in Wamena City, Jayawijaya Regency, Mountainous Papua Province - Raymond Feril Hattu; Mujiati Mujiati; Duha Awaluddin; Ira Widyastuti; Dewi Ana Rusim; Bernathius Julison (Publikasi Indonesia, 2024)
This study was conducted to determine the existence of subsurface aquifers and the distribution of groundwater-surface depth in Jayawijaya Regency, Mountainous Papua Province. The background of this research is the need for optimal groundwater management in areas with high topography such as Wamena City. The method used was a geophysical survey with the Wenner-Schlumberger configuration resistivity geoelectric technique to identify the aquifer layer. Primary data was obtained through direct measurements using geoelectric devices and GPS, while secondary data was obtained from related literature. The results showed that there were free aquifers with a depth of 25-105 meters and depressed aquifers at a depth of 145-270 meters in various research locations. The distribution of this aquifer is highly dependent on local geological conditions, with the availability of groundwater quite high in some areas and minimal in other areas such as Kampung Sabulama and Wasawa. In conclusion, the resistivity geoelectric method is effective for mapping the distribution of aquifers, which can further be used as a basis for groundwater management in the study area.